(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The research problem revolves around the level of reading comprehension among first-grade female students in the subject of "My Language," and how we can transform this weakness into reading skills and strengths. This transformation aims to make the students excellent models representing the sincerity of the research sample and to show how this sample contributed to developing previous performance into a notable advancement for this study. The theoretical framework focuses on reading comprehension as a cognitive mental process that involves understanding the meaning of words, sentences, paragraphs, distinguishing words, and recognizing linguistic elements. The aim of the research is to raise the level of reading comprehension and cognitive skills of first-grade female students in the subject of "My Language." The research serves as an important tool for improving the performance of teachers and preparing them to develop students’ reading comprehension skills. This underscores the importance of the question: Why do we want to develop students’ reading comprehension skills? The goal is to ensure that students progress through educational stages with full linguistic skills. The key findings of the research are as follows: 1. Enriching Arabic language curricula in early grades with intensive reading comprehension models. 2. Developing teaching methods for the subject "My Language" from traditional approaches to engaging and modern technological methods, which contribute to enhancing students’ reading comprehension. 3. Using modern technologies enhances the understanding and comprehension of reading among students in the subject "My Language". 4. Implementing modern technologies makes teaching the subject "My Language" more engaging and enjoyable. 5. Solving the reading comprehension problem by training students in modern reading comprehension methods. 6. Modern technologies help in understanding reading comprehension in the subject "My Language". 7. Using modern technologies simplifies the linguistic vocabulary of the subject "My Language".